Mainstreaming and Defamiliarizing the Rapture: The Leftovers Reads Left Behind - Walsh, Richard G. (Journal of the bible and its reception, 2024)
The popular Left Behind series has been credited with mainstreaming dispensational premillennialism, or fragments of that ideology, in U.S. popular culture. The less popular, but critically acclaimed HBO series The Leftovers , based on the novel of the same name by Tom Perrotta, attests to the ideology’s popularity while defamiliarizing its notions of Rapture and Messiah/Antichrist. While Left Behind apologizes for the ideology and strives to make the metanarrative’s identity attractive, entertaining, and thrilling, The Leftovers takes a "not quite" Rapture as its "what if" fictional starting point. The result embraces mystery, rather than apologetic certainty, and ordinary human life, rather than the supernatural. Fulfilled prophecy becomes confusion, coping, and possibly delusion. The metanarrative becomes unstuck fragments. Election (exceptional national and individual identities), miracle, and messiah are demythologized. Theodicy occurs only on a human level. At the same time, however, The Leftovers takes its "what if" seriously and sympathetically. Despite skepticism, its characters also understand the appeal of Rapture, Messiah, and the like as they too look for something sacred.